Susac's syndrome: an update. Issue 9 (6th February 2020) - Sauma, Johanna; Rivera, Daniela; Wu, Andres; Donate-Lopez, Juan; Gallego-Pinazo, Roberto; Chilov, Michael; Wu, Max; Wu, Lihteh
Abstract : Susac's syndrome (SS) is a relatively rare cause of multiple recurrent branch retinal arterial occlusions (BRAO). SS is frequently misdiagnosed and probably underdiagnosed. Ophthalmic manifestations may be the sole presenting sign of SS. Comprehensive literature review The typical triad of encephalopathy, sensorineural hearing loss and multiple recurrent BRAO is seldom seen at presentation in SS. The characteristic ophthalmological feature in SS is the presence of recurrent multiple BRAO in the absence of intraocular inflammation. Yellow to yellow-white, non-refractile or refractile retinal arterial wall plaques (Gass plaques) found at midarteriolar segments not associated to bifurcations are commonly found in SS. Because of its ability to capture more peripheral retinal area, ultrawide field fluorescein angiography (FA) has definite advantages over conventional FA and its use should be encouraged in patients suspected of having SS. Optical coherence tomography (OCT), particularly spectral domain OCT complements FA. Patients with BRAO and hearing loss that do not develop encephalopathy during the initial 2 years will most likely not develop encephalopathy. However, these patients will be prone to recurrent BRAO and hearing loss. Imunosuppression is the cornerstone of treatment but the best regimen still needs to be defined. A minority of patients with SS present with the typical triad. A high index of suspicion is needed to make the diagnosis promptly. Early diagnosis and treatment are important to delay disease progression and prevent blindness, deafness and dementia.